(3cJGH aj Gdabgs - (3eLghds
(3ChdgG (B:s
(3HSe Gddg (B.. (3cJGH GdeYGedGJ , hgh GdbSe GdKGfj ef CbSGe Gdabg dCfg jfbSe Edi CQHYI CbSGe YHGOGJ gj YHGQI YeG GTJQW aj UMJg GdfjI Ch eG TQY ddeUGdM GdCNQhjI Ch eG cGf ajg QLMGfjI TQYjI CUdjI Gh GdCYe efgG (B...s
(3BNQgG (B:s
.. (3Ydi GdeJjbf ef GdCdaGX eGOI hUhQI hhVYG hcjajI adG JCKjQ deLQO GdaYd heWdb Gdbhd hdG GdGSJjLGH hGdGjLGH Ydi GdeTghQ Hd XGgQge fbd GdELeGY ajg hgh Cf jbhd GdeTJQj HYfj ajbhd GdHGFY HYJc ef ZjQ Cf jQO GdeTJQj djchf(B..s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis